Nomos y physis. De la ley tradicional y la naturaleza en el mundo de Estados de Tucídides (Iter, 2022)
In the Greek world of the 5th century BC, Nomos and associated concepts sufferthe confrontation of Physis, which can represent a stronger law. In the work of Thucydides, appealing to the nature seems normal in the field of relations betweenStates. Although there are actors in this field that prefer to invoke the nomos inthe sense of a moral law or customary use, it may be no more than fine words thathave no force in the reality (the erga). In the internal order of a State, traditionalnomos retains its validity, except when a revolutionary crisis trasvalore its meaningand simply force prevails. And in an order that is located between the inner andthe outer, the political chief can not act simply according to the moral values thathe can appreciate; because he acts in a field in which governs the law of nature, hehas to meet requirements higher than the private virtue. Nomos and Physis are thusintertwined in the Thucydidean work, at times in tragic way.
Keywords: Ancient Greece – Thucydides – Law – Nature – International Relations - Crisis